Knowledge, skills, and attitudes as predictors in determining teachers' competency in Malaysian TVET institutions - Omar, Muhd Khaizer; Zahar, Farah Nadia; Mat Rashid, Abdullah (Horizon Research, 2020)
Teachers' competency has sparked much interest among educational stakeholders in Malaysia. The debates among how well Malaysian teachers educate students has produced concern and become interminably reported in research. Under the government civil servants' services, teachers have been called upon to gain and bringing back this noble and reputable profession at its standard and earn the trust of parents in ensuring the success of their children at school. As part of this matter, TVET stream in Malaysia becomes sensational and selected as one of the national agendas in producing the local manpower and human capital development, where the spirit is to grow the young generation to become a skilled-worker in industry. Indeed, encumbrance issues such as teacher competency, program accreditation, and unemployment among graduates are among those matters mostly brought into round-table discussions and conversations among stakeholders. Therefore, this article depicted one of the issues, which is on the basis of teachers' competency and analyzed the relationship between teacher's competency traits (knowledge, skills, attitude) and teaching practices in practical-based learning and also to discover the best predictor contributed to teacher's competency measurement. A survey was distributed to 150 TVET teachers at three selected vocational colleges in Selangor. The construct of the questionnaire was adapted from prior studies and undergone a pilot study to ensure the questionnaire fit with intended research objective. The results of the study revealed that knowledge, skills, and attributes have played a major role in ensuring the competency level of Teachers. Along with the findings, the knowledge of the teachers was found the most critical factor to describe TVET teacher’s competency. The implication of the results suggested that holistic traits of teacher that in knowledge, skills, and attitudes inclusively empower, their competency level of becoming effective teachers. Notwithstanding the need for the development of skilled manpower must conclusively enlighten not only knowledge-based but also students' discovery of their skills and attitude potential especially when entering the job environment. Therefore, before proceeding with the teaching and learning environment, the teacher must first imply all these characteristics and exercise this application to students. Ultimately, the outcome from this environment will help students to venture the employment market and increase the likeliness of getting hired; locally and global job market.